International perspectives on early childhood research : a day in the life - Gillen, Julia; Cameron, Catherine (Catherine Ann) (Basingstoke, England : Palgrave MacMillan, 2010)
'An international team of researchers videoed a day in the life of two-and-a-half-year-old girls at home in Canada, Italy, Peru, Thailand, Turkey, the UK and the USA. Different paths to wellbeing are illustrated through words and images. The book examines how human culture is shaped through interactions involving young children and their families'--Provided by publisher.
Includes bibliographical references (p. 180-193) and index.
Keywords: Children -- Cross-cultural studies